Impact of radiotherapy on surgical repair and outcome in patients with rectourethral fistula. (December 2013) - Beddy, D.; Poskus, T.; Umbreit, E.; Larson, D. W.; Elliott, D. S.; Dozois, E. J.
Abstract Aim Most patients presenting with rectourethral fistula acquire it as a complication of radiotherapy for prostate cancer, as a result of injury to the rectum during prostatectomy, through trauma or from Crohn's disease. This study examined whether choice of operation and results of surgery for rectourethral fistula are influenced by prior radiotherapy. Method Male patients undergoing surgery for rectourethral fistula were identified from a prospectively maintained database. Data regarding aetiology, surgical treatment and outcomes were analysed. Results Fifty patients (median age = 65.5 years) were identified. Radiation was received by 29 patients for prostate or rectal cancer, and 21 patients developed a fistula following prostatectomy, Crohn's disease or pelvic fracture (without radiation). Prior to definitive surgery, 30 patients underwent fecal diversion and 37 underwent urinary diversion. In total, 57 repairs were performed (44 patients had one repair, five patients had two and one patient had three). Definitive surgery was approached predominantly abdominally in radiated patients (90.6 vs 9.3%, P < 0.001) and perineally in nonradiated patients (80 vs 20%, P < 0.001). Successful primary fistula repair was more frequent in the nonradiated group compared with the radiated group (80.9 vs 0%, P < 0.001). Permanent colostomy and urinary diversion were more often required in radiated patients than in nonradiated patients (colostomy: 83 vs 0%, P < 0.001; urorostomy: 100 vs 19%, P < 0.001). Conclusion Few patients with radiation‐induced rectourethral fistula avoid permanent colostomy and urostomy. In contrast, most patients with nonradiation‐related fistulae undergo successful perineal repair without permanent faecal and urinary diversion.